Relationship of different intensities of physical activity and quality of life in postmenopausal women - Felipe, Juliana [UNESP]; Viezel, Juliana [UNESP]; Reis, Andréa Dias [UNESP]; Da Costa Barros, Emili Amice [UNESP]; De Paulo, Thais Reis Silva; Neves, Lucas Melo; Júnior, Ismael Forte Freitas [UNESP] (Springer Nature, 2020)
Background: It is known that the elderly population remains most of the time in light activity. Physical activity plays a key role in the primary prevention of chronic diseases to mitigate various deleterious effects of aging and improve quality of life. The objective of the present study was to evaluate whether the time that postmenopausal women remain in light activities during the day are related to better quality of life and compare these results with the quality of life of those who remain longer in moderate intensity and vigorous activity. Methods: This is a cross sectional study there were evaluated 102 women, aged 50 to 79 years, all postmenopausal. Physical activity was measured by triaxial accelerometers. The quality of life was assessed using a Brazilian validated version of the SF-36 questionnaire. The sample was divided in three groups (G1, G2 and G3) according to tercile of time spent per week on light, moderate and moderate+vigorous physical activity. The comparisons between groups were made by ANOVA One Way, and the relationship between variables were made through the Spearman's correlation coefficient, and the significance was set at 5%. Results: We found that the amount of time of light physical activity shows a higher correlation values compared to the moderate and moderate+vigorous physical activity (p < 0,05) and presented significant correlation in all domains of quality of life. Vigorous physical activity did not presented significant correlation in all domains of quality of life. Conclusion: Our data suggests that light intensity physical activity presented influence on the quality of life of postmenopausal women. Trial registration: (NCT02804308). Registered on 17 june 2016 (retrospectively registred).
Keywords: Level of physical activity; Postmenopausal women; Quality of life